Effect of Cardiac Resynchronization Therapy (CRT) on Six-Minute Walk in Patients with Heart Failure and Left Bundle Branch Block - Hameedullah; Khan, Zahoor Ahmad (Journal of Postgraduate Medical Institute, 2024)
Objectives: To study the outcomes of cardiac resynchronization therapy (CRT) on the 6-minute walk test, in patients presenting with heart failure (HF) and left bundle branch block (LBBB). Methodology: After getting approval from Institutional Ethical Board, this descriptive cross secitonal study was conducted at Cardiology Department of Hayatabad Medical Complex, Peshawar from 1st Jan 2023 to 30th June 2023. The study consisted of 50 patients, who met the inclusion criteria. Each patient underwent an extensive clinical assessment prior to cardiac resynchronization therapy (CRT) implantation. This consisted of a comprehensive clinical assessment involving detailed medical history taking, New York Heart Association (NYHA) functional class evaluation, and their documentation of their medications. Results: A total of 50 heart failure (HF) patients with the left bundle branch block (LBBB) were enrolled, with a baseline average age of 50 ± 9.9 years. On 6-Minute Walk Test (6MWT), post-cardiac resynchronization therapy (CRT) the mean increase in the walk test distance was 60, 75 and 80 meters on 3 month, 6 month and 12 month follow-up, respectively. Post-CRT, there was a notable increase in mean Left ventricular ejection fraction (LVEF) from 35 ± 5% at baseline to 40 ±10.0 % at 6 months and to 50.0% at 12 months. The mean duration of the QRS complex also reduced from more than 135 msec to 110 msec at post-CRT 12 months. At the start of the study, 40 patients were in New York Heart Association (NYHA) functional class 3. Post CRT at 12 months,about 25 patients improved and shifted to NYHA functional class 2 and 10 patients shifted to NYHA functional class 1. Conclusion: There is a substantial increase in the mean distance post-cardiac resynchronization therapy (CRT) on 6-Minute Walk Test (6MWT). It could markedly reduce the duration of prolonged QRS and improve Left ventricular LV function in patients presenting with heart failure (HF) and left bundle branch block (LBBB). These advantages can enhance patients' quality of life (QOL) and clinical outcomes.